Analysis of the correlation between science literacy and critical thinking of grade eight students in the circulatory system - Dewi Asriani Ridzal; Haswan Haswan (Jurnal Pijar Mipa, 2023)
This study aimed to analyze the relationship between scientific literacy and students' critical thinking skills in biology science material in junior high schools. The research used a quantitative correlation method. The subjects in this study were the students in the eighth grade of junior high school SMPN 9 Buton consisted of 68 people. The research instrument was in the form of multiple choice questions to measure scientific literacy skills and essay questions to measure students' critical thinking skills. The research data obtained were then analyzed with descriptive and inferential statistics through the product-moment correlation test. Results of descriptive statistics show that literacy science and student critical thinking there in four criteria excellent, good, enough, and low. The inferential statistic analysis results show that the significance value of the correlation between scientific literacy and critical thinking skills is 0.001 less than the alpha value of 0.05. Based on the results can be concluded there is a positive and significant correlation between scientific literacy and students' critical thinking skills in the circulatory system material.